Choosing award criteria : preferences and policies - Marttila, Henna (My University, 2022)
Public procurement covers a significant share of state expenditure in the European Union. Under EU Directives for public procurement, public contracts shall be awarded on the basis of sole price or combinations of price and quality considerations. During the legal and judicial development of these Directives the EU has actively promoted the usage of quality award criteria. However, Member State reports have shown that the contracting authorities in Member States are prone to favouring sole price award criterion instead of quality criteria. This thesis concerns the reasons for this preference and limitations for it. Research method for this thesis was dogmatic. In this thesis it was found that the legislative regime suffers from legal uncertainty which may affect the Member States’ willingness in using quality award criteria due to its complexity. It was found that the EU is willing to promote using quality award criteria to support Union-wide policies, but those policies are not always in line with the policy choices or preferences of the Member States. Furthermore, the current legislative regime is internally obscure and does not offer clarity on the status of general principles of procurement and their limitations on setting award criteria. The CJEU judicial line in these matters leaves some important questions unaddressed while others are interpreted widely, sometimes also in an expansive and active manner – sometimes at the cost of predictability. Moreover, it is not clear whether it is overall beneficial to assess quality as an award criterion in some procurement activities. The conflict between EU and national preferences in public procurement is imminent and the legal environment calls for updates. Due to the institutional turbulence in law-making it is clear that new legislation is hard to create. Because many of the challenges arising in contract award criteria concern strongly national interests, it does not seem likely that these differing preferences can coexist in EU public procurement at all.
Keywords: public procurement, award criteria, most economically advantageous tender